2019
DOI: 10.4067/s0034-98872019000300281
|View full text |Cite
|
Sign up to set email alerts
|

El tratamiento postnatal con melatonina modula la expresión de agentes prostanoides en pulmón de neonatos de oveja con hipertensión pulmonar

Abstract: Melatonin modulates the expression of pulmonary prostanoids Background: Living above 2,500 meters in hypobaric conditions induces pulmonary arterial hypertension of the neonate (PAHN), a syndrome whose main features are: pathological remodeling of the pulmonary vessels, abnormal vascular reactivity and increased oxidative stress. Melatonin could have pulmonary antioxidant, anti-remodeling and vasodilating properties for this condition. Aim: To determine the effect of melatonin at the transcript level of prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The latter was associated with increased nitric oxide -dependent and -independent vasodilator functions. Interestingly, one of the nitric oxide independent affected mechanisms, was the enhanced expression of the prostacyclin vasodilator pathway [3,4]. The aforementioned findings were also associated with increased expression and/or activity of the endogenous antioxidant enzymes, superoxide dismutase and catalase, an enhanced plasma antioxidant capacity and a marked decreased in pulmonary oxidative stress markers [2,3].…”
mentioning
confidence: 98%
“…The latter was associated with increased nitric oxide -dependent and -independent vasodilator functions. Interestingly, one of the nitric oxide independent affected mechanisms, was the enhanced expression of the prostacyclin vasodilator pathway [3,4]. The aforementioned findings were also associated with increased expression and/or activity of the endogenous antioxidant enzymes, superoxide dismutase and catalase, an enhanced plasma antioxidant capacity and a marked decreased in pulmonary oxidative stress markers [2,3].…”
mentioning
confidence: 98%
“…Our findings may explain previous studies that described the direct vasodilator effects of melatonin [ 33 , 78 ]. In addition, melatonin modulates the release of NO, reducing peroxynitrite formation and offer protection from nitrosative/oxidative damage [ 78 ], as well as favoring an increased vasodilation in pulmonary arteries via COX1-PGIs-IP pathway [ 79 ]. Studies undertaken in several animal models have indicated that melatonin has dual effects on the vasculature, with vasoconstriction being observed through MT1 receptor activation and vasodilatation through MT2 receptor [ 28 , 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further details have been reviewed elsewhere (40). Two recent pre-clinical studies concern protection by melatonin in the perinatal phase of lambs (41,42) and are of particular interest to corresponding investigations in humans (cf. subsequent section).…”
Section: Introductionmentioning
confidence: 99%
“…subsequent section). Melatonin was administered to lambs born at an altitude of 3,600 meters, i.e., under hypobaric conditions, between 4 and 21 postnatal days (41). In these animals, melatonin enhanced the expression of prostacyclin synthase mRNA and prostacyclin receptor at protein level, components of a vasodilator pathway, whereas vasoconstriction via the thromboxane pathway was not affected.…”
Section: Introductionmentioning
confidence: 99%